2000
DOI: 10.1073/pnas.100113397
|View full text |Cite
|
Sign up to set email alerts
|

The yeast A kinases differentially regulate iron uptake and respiratory function

Abstract: Tpk2, but not Tpk1 or Tpk3, is required for pseudohyphal growth. Genome-wide transcriptional profiling has revealed unique signatures for each of the three A kinases leading to the identification of additional functional diversity among these proteins. Tpk2 negatively regulates genes involved in iron uptake and positively regulates genes involved in trehalose degradation and water homeostasis. Tpk1 is required for the derepression of branched chain amino acid biosynthesis genes that seem to have a second role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
154
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(163 citation statements)
references
References 36 publications
8
154
1
Order By: Relevance
“…This implies as well that there is probably a large overlap in the functions of Tpk1-3, which is further consistent with the high level of protein sequence similarity between the different catalytic subunits (Toda et al 1987b). Nevertheless, there are several examples of separate, specific functions for the different subunits, such as the induction of pseudohyphal growth, the expression control of genes involved in iron uptake or branched amino acid biosynthesis, or the regulation of mitochondrial enzymes (Robertson and Fink 1998;Pan and Heitman 1999;Robertson et al 2000;Zhu et al 2000;Singh et al 2004;Chevtzoff et al 2005;Ptacek et al 2005). Given their central and essential role, the activity of the catalytic subunits is tightly regulated.…”
Section: Transducing the Glucose Signal To Snf1supporting
confidence: 57%
“…This implies as well that there is probably a large overlap in the functions of Tpk1-3, which is further consistent with the high level of protein sequence similarity between the different catalytic subunits (Toda et al 1987b). Nevertheless, there are several examples of separate, specific functions for the different subunits, such as the induction of pseudohyphal growth, the expression control of genes involved in iron uptake or branched amino acid biosynthesis, or the regulation of mitochondrial enzymes (Robertson and Fink 1998;Pan and Heitman 1999;Robertson et al 2000;Zhu et al 2000;Singh et al 2004;Chevtzoff et al 2005;Ptacek et al 2005). Given their central and essential role, the activity of the catalytic subunits is tightly regulated.…”
Section: Transducing the Glucose Signal To Snf1supporting
confidence: 57%
“…The regulation of genes that facilitate iron uptake in C. albicans has been reported to be under the control of the CaTup1p transcriptional repressor (Knight et al, 2002). Interestingly, cDNA micro-arrays have shown that transcriptional repression of ScFRE2, ScFET3, ScFTR1, ScCCC2 and the ScARN genes in response to high-iron conditions in S. cerevisiae is under the control of the protein kinase ScTpk2p (Robertson et al, 2000). The ScTPK2 gene and its functional homologue in C. albicans are also involved in the regulation of morphogenesis via the cAMP-activated pathway (reviewed by Gancedo, 2001;Sonneborn et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although the PKA catalytic subunits, encoded by TPK1, TPK2, and TPK3, are redundant in most cases, they sometimes show different substrate specificities and functions (40)(41)(42). To determine whether a specific PKA subunit controls Sfp1 nuclear localization, we generated strains containing a single PKA catalytic subunit and lacking the regulatory subunit Bcy1.…”
Section: Regulation Of Sfp1mentioning
confidence: 99%